Upadacitinib sustained-release tablets for the treatment of chronic refractory gouty arthritis: a case report and literature review - Yu, Lishi; Huang, Weidong; Lv, Honghua; Jin, Lie; Lei, Wenhui (Frontiers in Medicine, 2024)
Background：Gouty Arthritis(GA) is a crystal-related joint disease caused by the deposition of monosodium urate (MSU) crystals, directly associated with hyperuricemia resulting from purine metabolism disorder and/or reduced uric acid excretion. Acute attacks of typical gouty arthritis are generally relieved through the clinical use of NSAIDs, colchicine, or glucocorticoids. However, managing patients with chronic refractory gout poses challenges due to complications such as multiple tophi, gouty nephropathy, diabetes, and gastrointestinal bleeding. While there have been numerous studies on gout in recent years, research specifically regarding chronic refractory gout remains limited. The management of such cases still faces several unresolved issues, including recurrent disease flare-ups and poor patient compliance leading to inadequate drug utilization and increased risk of side effects. In this report, we present a case of successful improvement in chronic refractory gouty arthritis using the biologic agent upadacitinib sustained-release tablets.Case Presentation: Our case report involves a 53-year-old Asian patient with recurrent gouty arthritis who had a history of over 20 years without regular treatment, presenting with tophi and an increasing number of painful episodes. During hospitalization, various analgesics and anti-inflammatory drugs provided inadequate relief, requiring the use of steroids to alleviate symptoms. However, tapering off steroids proved challenging. We decided to add upadacitinib sustained-release tablets to the treatment regimen, which ultimately improved the patient's condition. After six months of follow-up, the patient has not experienced any further acute pain episodes.This case highlights the potential therapeutic effect of upadacitinib sustained-release tablets during the acute phase of chronic refractory gouty arthritis.